GENERAL CHARACTERISTICS OF ADMINISTRATIVE OFFENCES IN THE FIELD OF DRUGS AND PSYCHOTROPIC SUBSTANCES’ TRAFFICKING - Zykin, Boris (Administrative and Criminal Justice, 2019)
Drug addiction is an extremely acute social problem and it attracts the attention of both legal scholars and practitioners. This is due to the fact that the improvement of the measures’ system aimed at preventing and stopping the spread of the drugs and psychotropic substances requires the joint efforts of specialists in various fields.Despite a slight decrease in crime rates, a study of the current state of the administrative and legal measures’ application aimed at preventing and stopping the unauthorized distribution of narcotic drugs and psychotropic substances shows that these measures do not yet sufficiently provide solutions for increasing the activity and effectiveness of the struggle against drug addiction, prevention and elimination of this phenomenon’s socially dangerous consequences.The struggle against drug abuse by administrative and legal measures needs to be improved and must correspond to the prevailing socio-economic conditions. In this regard, the application of administrative and legal measures aimed at preventing and stopping the spread of drugs and psychotropic substances in our country requires further theoretical study of issues related to their concept, purpose and implementation.